Hetero-bimetallic metal–organic polyhedra. Issue 2 (30th October 2015) - Teo, Jesse M.; Coghlan, Campbell J.; Evans, Jack D.; Tsivion, Ehud; Head-Gordon, Martin; Sumby, Christopher J.; Doonan, Christian J.
Abstract : Porous metal–organic polyhedra (MOPs), constructed from heterometallic Pd II –M II (M = Cu, Ni, Zn) paddlewheel nodes and 5- tert -butyl-1, 3-benzenedicarboxylate organic links, were prepared in which the Pd II ions preferentially line the inner surface of the cage molecules. Abstract : Porous metal–organic polyhedra (MOPs), constructed from heterometallic Pd II –M II (M = Cu, Ni, Zn) paddlewheel nodes and 5- tert -butyl-1, 3-benzenedicarboxylate organic links, were prepared in which the Pd II ions preferentially line the inner surface of the cage molecules. Careful activation produces co-ordinatively unsaturated 3d transition metal sites on the external MOP surfaces giving rise to H2 adsorption enthalpies in excess of −12 kJ mol −1 .